2009
DOI: 10.1097/jto.0b013e3181914111
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of EGFR, KRAS, and TP53 Gene Mutations in a Large Cohort of Japanese Patients with Surgically Treated Lung Adenocarcinoma

Abstract: EGFR, KRAS, and TP53 gene mutations were not independently associated with the prognosis for Japanese patients with surgically treated lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
166
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(200 citation statements)
references
References 26 publications
28
166
0
6
Order By: Relevance
“…Of these TFs, TP53 and PGR have high expression in the two subtypes while SP3, SMAD4 and ESR2 have low expression, which suggesting that these TFs may play an important role both in AC and SCC. These expression profiles also found in previous studies (Takahashi et al, 1989;Bodner et al, 1992;Kosaka et al, 2009) of lung cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Of these TFs, TP53 and PGR have high expression in the two subtypes while SP3, SMAD4 and ESR2 have low expression, which suggesting that these TFs may play an important role both in AC and SCC. These expression profiles also found in previous studies (Takahashi et al, 1989;Bodner et al, 1992;Kosaka et al, 2009) of lung cancer.…”
Section: Discussionsupporting
confidence: 88%
“…This study was restricted to patients who had no adjuvant or neoadjuvant systemic therapy administered and focused solely on the postoperative prognostic differences among different genotypes. On the other hand, Kosaka et al reported that the significant prognostic impact of EGFR mutations was lost after adjusting for other confounding prognostic factors (4). Several other studies in the literature corroborate this finding (5,6).…”
supporting
confidence: 74%
“…It is to be noted that both EGFR mutation subtypes promoted lung adenocarcinomas with lepidic growth features in transgenic mice (13). Table 1 summarizes ten studies that reported a relationship between EGFR mutation subtypes and prognosis (4,5,11,(14)(15)(16)(17)(18)(19)(20)(21). In focusing on the association between DFS or recurrence and EGFR mutation subtype, Liu et al also reported that patients with Stage I-IIIA lung adenocarcinoma harboring Ex19 had a better DFS rate than those with Ex21 (P=0.056) (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall response rates were as high as 80% in patients harboring mutations compared with p10% in patients with wildtype EGFR (Huang et al, 2004;Lynch et al, 2004;Mu et al, 2004;Paez et al, 2004;Pao et al, 2004; Sasaki et al, 2006;Kosaka et al, 2007;Yoshida et al, 2007;see Gazdar, 2009).…”
Section: Egfr Mutations As Biomarkersmentioning
confidence: 99%